Employee Engagement, Training and Career Development (Tata Tele Services Limited – A Case Study) - Vashistha, Shikha (Journal of Commerce and Trade, 2016)
Employee engagement is generally the level of commitment and involvement an employee has towards his or her organization and its core values and beliefs. An engaged employee is presumed to be aware of business context, and work dynamics with colleagues and peer groups to improve performance within the job for the benefit and excellence of the organization. It is a positive attitude held by the employees towards the organization and its values. The paper focuses on how employee engagement is an antecedent of job involvement and what should a company do to make the employees engaged. The scope of the study is limited to one organisation i.e. Tata Tele Services which is one of the major players in the Indian services sector. The paper attempts to do an analysis of employee engagement strategies adopted by the organisation on the basis of the widely accepted Ten Cs Model of Employee Engagement.